(3JMaI GdRGFQ aj SjQI GdCejQ YHO GdbGOQ hCNHGQ GdLRGFQs - (3GdLRGFQj, YHO GdbGOQ eMjj GdOjf Hf eUWai, J(B1300(3g`s
(3ChdgG (B:s
(3PcQ QchH GdCejQ GdHMQ hhUhdg Edi Whdhf heG GJab eY OhdI aQfSG hKGdK jh hUhdg EdiGeY GdZRhGJ SGQ HCgdgs
(3BNQgG (B:s
(3hbdI GdQhGjI hcdGd GdOQGjI, gPG eY eG fMf Ydjg ef TZd GdHGd hGdJfbd aj GdMjQI ef MGd Edi MGds
(3GdJhKjbGJ GdeQLYjI (B:s
(3GdCYdGe(B: 4 / 45s
(3eYLe GdeDdajf(B: 2 / 198s
(3eUOQ GbJfGA GdCUd (B:s
(3OGQ GdcJH GdbWQjIs
(3ehGUaGJ GdhYGA (B:s
Keywords: (3GdJGQjNs